Optimization of Cyclodextrin Loaded Lornoxicam Fast Dissolving Tablets Using Box- Behnken Design: Pharmaceutical Science-Pharmaceutics - Rao, M.Trinadha; M.Yamini; Phanindra, Ch.V.S.; Mallikarjun, P.N.; Kamalakumari, P.V.; Srinivasa Rao, Y. (International Journal of Life Science and Pharma Research, 2022)
The present investigation was undertaken in the design and evaluation of fast dissolving tablets of the Non-Steroidal antiinflammatory drug Lornoxicam. Lornoxicam is an orally bio available oxicam derivative with anti inflammatory, antipyretic and analgesic properties upon oral administration. The main aim of this study is to prepare mouth dissolving tablets of hydroxyl propyl ß cyclodextrin loaded lornoxicam by Box-Behnken design. The main objective is to enhance the solubility, palatability of Lornoxicam by using cyclodextrin as a complexing agent and optimize the formulation by using Box-Behnken design.The inclusion complexes of Lornoxicam were prepared by physical mixture and solvent evaporation method by using drug and HP ß cyclodextrin in various ratios (1:1 and 1:2). Dissolution study was carried out for the 2 ratios of kneading method and solvent evaporation method. 1:1 ratio of solvent evaporation method was selected for the optimization by Box-Behnken design. The selected inclusion complexes were then utilized for the preparation of tablets by direct compression. The independent variables are lactose, sodium starch glycolate and crospovidone. The dependent factors studied were wetting time, in vitro disintegration, in vivo disintegration and in vitro dissolution. Optimized Formulae were prepared and evaluated for in vitro dissolution characteristics, in vitro disintegration time, wetting time, and their physico-mechanical properties. The predicted formula formulated with the Box-Behnken statistical design consisted of lactose, sodium starchglycolate and crospovidone at the optimum levels of 30, 20 and 20 mg respectively which is considered as the best optimized formulation with good dissolution profile. The bioavailability has been increased from the optimized formulation. The formulation was evaluated for stability.From the research a taste masked mouth dissolving tablet formulation is selected to increase patient compliance with enhanced solubility, dissolution and stability.